Developmental plasticity of spatial hearing following asymmetric hearing loss: context-dependent cue integration and its clinical implications - Keating, Peter; King, Andrew J. (Frontiers in Systems Neuroscience, 2013)
Under normal hearing conditions, comparisons of the sounds reaching each ear are critical for accurate sound localization. Asymmetric hearing loss should therefore degrade spatial hearing and has become an important experimental tool for probing the plasticity of the auditory system, both during development and adulthood. In clinical populations, hearing loss affecting one ear more than the other is commonly associated with otitis media with effusion, a disorder experienced by approximately 80% of children before the age of two. Asymmetric hearing may also arise in other clinical situations, such as after unilateral cochlear implantation. Here, we consider the role played by spatial cue integration in sound localization under normal acoustical conditions. We then review evidence for adaptive changes in spatial hearing following a developmental hearing loss in one ear, and argue that adaptation may be achieved either by learning a new relationship between the altered cues and directions in space or by changing the way different cues are integrated in the brain. We next consider developmental plasticity as a source of vulnerability, describing maladaptive effects of asymmetric hearing loss that persist even when normal hearing is provided. We also examine the extent to which the consequences of asymmetric hearing loss depend upon its timing and duration. Although much of the experimental literature has focused on the effects of a stable unilateral hearing loss, some of the most common hearing impairments experienced by children tend to fluctuate over time. We therefore argue that there is a need to bridge this gap by investigating the effects of recurring hearing loss during development, and outline recent steps in this direction. We conclude by arguing that this work points toward a more nuanced view of developmental plasticity, in which plasticity may be selectively expressed in response to specific sensory contexts, and consider the clinical implications of this.